1981
DOI: 10.1017/s0003356100024934
|View full text |Cite
|
Sign up to set email alerts
|

Beef production from silage 2. The performance of beef cattle given silages of either perennial ryegrass or red clover

Abstract: 1.A primary growth of perennial ryegrass was cut on 8 to 11 May (early) or on 12 June (late) for comparison with the primary growth of a tetraploid red clover, which was cut either on 1 or 2 June (early) or on 28 June (late). The crops were ensiled, after wilting for about 4h, with the addition of formic acid at 2-21/t fresh crop. The silages were given ad libitum alone or with rolled barley at 11-5 g dry matter per kg live weight to 40 British Friesian steers initially 3 months old and 108 kg live weight. 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
3
18
3
Order By: Relevance
“…-~_ _ _ _ was consistent with values derived from an earlier experiment (Thomas et al 1981) where cutting was delayed for a similar period. Increasing the proportion of barley given with the late-cut silage led to a progressive increase in the digestibility of the DM and gross energy, similar to that observed by Vadiveloo & Holmes (1979) with hay-based diets.…”
Section: Apparent Digestibility and Intakesupporting
confidence: 86%
“…-~_ _ _ _ was consistent with values derived from an earlier experiment (Thomas et al 1981) where cutting was delayed for a similar period. Increasing the proportion of barley given with the late-cut silage led to a progressive increase in the digestibility of the DM and gross energy, similar to that observed by Vadiveloo & Holmes (1979) with hay-based diets.…”
Section: Apparent Digestibility and Intakesupporting
confidence: 86%
“…Total DM intakes, expressed on a percent BW basis for grass and red clover脕timothy silages were similar to values reported by Berthiaume et al (2006) for cattle fed grass silage. However, these intakes were lower than values reported by others (Day et al 1978;Thomas et al 1981;Steen and McIlmoyle 1982) for grass-and red clover silages fed to British Friesian steers, where intakes were greater for cattle fed red clover versus grass silages. Differences in intake resulted in greater gains for cattle fed red clover silages and were attributed to variation in silage fermentation, wilting and maturity at harvest (Steen and McIlmoyle 1982), as well as to animal factors, such as age and breed.…”
Section: Growth Performancecontrasting
confidence: 61%
“…Lower average daily gains for tall fescue-versus red clover脕timothy silage fed cattle in the present study may be due to lower crude and soluble protein contents of tall fescue silage (Table 1). Greater gains in cattle fed red clover versus grass silage in the past (Day et al 1978;Thomas et al 1981) were also associated with higher N contents for red clover silages. While Noviandi et al (2012a) found that nitrogen fertilization of tall fescue increased crude protein content of pasture and subsequent gains by grazing steers as compared with tall fescue pastures that were not fertilized, this was not an issue in the present study as tall fescue fields were fertilized with nitrogen.…”
Section: Growth Performancementioning
confidence: 99%
“…Mixtures also have higher soluble carbohydrate THE POTENTIAL OF TETRAPLOID red clover was contents, a better balance nutritionally and reviewed by Frame (1976) who concluded diluted oestrogenic activity; weed ingress is that its ability to provide high yields (10 to limited and clover crowns are cushioned 12 t dry matter (DM) per ha) of protein-rich against wheel damage (Frame, 1975). When used as silage, it is suggested and Copeman, 1976; Tayler and Wilkins, that it should be grown with a companion grass 1976; Day, Harkess and Harrison, 1978; as grass/clover mixtures, which give higher DM Thomas, Aston, Gibbs and Tayler, 1981a; and digestible organic matter (DOM) yields Thomas, Gibbs and Tayler, 1981b; Steen and but lower crude protein (CP) yields than pure Mcllmoyle, 1982a). efficiency of conversion characteristics made it Most feeding trials to date with beef cattle a highly acceptable forage for livestock.…”
Section: Introductionmentioning
confidence: 99%